Sosialisasi Pelestarian Terumbu Karang Berbasis Biorock - Ratna; F.Hardianti; E. Loupatty; R.M.Linta; N. Ayomi; F.Mahad; R. Sangaji; A.M.Suruwaky; M. S. Rumwokas; Fahrizal, Ahmad (Lembaga Pengembangan dan Pengabdian Masyarakat Universitas Muhammadiyah Sorong, 2025)
The socialization activity on coral reef conservation using Biorock technology was conducted at MA Emayodere Sorong as an environmental education initiative for the younger generation. The purpose of this activity was to enhance students’ understanding and awareness of the importance of marine ecosystem conservation, particularly coral reefs, and to introduce Biorock technology as an innovative solution for reef rehabilitation. The activities were carried out through interactive presentations, group discussions, and evaluations using pre-tests and post-tests. The results showed a significant improvement in students’ understanding. The average pre-test score of 55 increased to 82 in the post-test, representing a 27-point or 49% improvement. A total of 88% of the students expressed increased concern for marine environmental issues, and 72% showed interest in participating in conservation actions. This activity demonstrates that an educational approach combining technology and participation can effectively foster environmental awareness among students. Therefore, the socialization of coral reef conservation using Biorock technology is not only effective in enhancing students’ knowledge but also holds the potential to create young environmental change agents. Such activities should be continued sustainably with cross-sectoral support to protect marine ecosystems.